Addressing illegal longlining and ghost fishing in the Galapagos marine reserve: an overview of challenges and potential solutions - Castrejón, Mauricio; Defeo, Omar (Frontiers in Marine Science, 2024)
Despite regulations aimed at curbing shark finning and bycatch, shark fishing mortality rates continue to escalate, partly due to unintended consequences of these policies which, along with illegal, unreported, and unregulated fishing and ghost fishing, undermine conservation efforts. The ineffectiveness of current regulations to curb shark mortality highlights the pressing need for reevaluating shark conservation strategies, especially in ecologically sensitive areas. In this context, the debate on enforcing longlining bans in multiple-use marine protected areas, including shark sanctuaries, is intensifying. Some argue for total bans to minimize incidental shark mortalities, while others highlight the socioeconomic importance of longlining, advocating for alternative conservation measures. In 2000, longline fishing was banned in the Galapagos Marine Reserve (GMR) as a precautionary measure to prevent illegal fishing of sharks and bycatch of endangered, threatened, and protected species. After 24 years of enforcement, official and anecdotal evidence indicate that illegal small-scale tuna longlining and ghost fishing are increasing threats across the reserve. This paper provides an overview of the longline fishing controversy within the GMR, incorporating scientific evidence, legal and socioeconomic considerations, and perceptions from the Galapagos small-scale fishing community. We offer novel insights and recommendations for the development of the Galapagos small-scale tuna fishery within an ecosystem approach to fisheries. This approach aims to reconcile conservation goals with the needs of local communities, while also proposing innovative solutions to address the longstanding debate surrounding longlining in the GMR.